Household acquisition and transmission of extended-spectrum β-lactamase (ESBL) -producing Enterobacteriaceae after hospital discharge of ESBL-positive index patients. (September 2021) - Riccio, Maria E.; Verschuuren, Tess; Conzelmann, Nadine; Martak, Daniel; Meunier, Alexandre; Salamanca, Elena; Delgado, Mercedes; Guther, Julia; Peter, Silke; Paganini, Julian; Martischang, Romain; Sauser, Julien; et al.
Abstract: Objectives: This study aimed to determine rates and risk factors of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) acquisition and transmission within households after hospital discharge of an ESBL-PE-positive index patient. Methods: Two-year prospective cohort study in five European cities. Patients colonized with ESBL-producing Escherichia coli (ESBL-Ec) or Klebsiella pneumoniae (ESBL-Kp), and their household contacts were followed up for 4 months after hospital discharge of the index case. At each follow up, participants provided a faecal sample and personal information. ESBL-PE whole-genome sequences were compared using pairwise single nucleotide polymorphism-based analysis. Results: We enrolled 71 index patients carrying ESBL-Ec ( n  = 45), ESBL-Kp ( n  = 20) or both ( n  = 6), and 102 household contacts. The incidence of any ESBL-PE acquisition among household members initially free of ESBL-PE was 1.9/100 participant-weeks at risk. Nineteen clonally related household transmissions occurred (case to contact: 13; contact to case: 6), with an overall rate of 1.18 transmissions/100 participant-weeks at risk. Most of the acquisition and transmission events occurred within the first 2 months after discharge. The rate of ESBL-Kp household transmission (1.16/100 participant-weeks) was higher than of ESBL-Ec (0.93/100 participant-weeks), whereas more acquisitions were noted for ESBL-Ec (1.06/100 participant-weeks) compared with ESBL-Kp (0.65/100 participant-weeks). Providing assistance for urinary and faecal excretion to the index case by household members increased the risk of ESBL-PE transmission (adjusted prevalence ratio 4.3; 95% CI 1.3–14.1). Conclusions: ESBL-PE cases discharged from the hospital are an important source of ESBL-PE transmission within households. Most acquisition and transmission events occurred during the first 2 months after hospital discharge and were causally related to care activities at home, highlighting the importance of hygiene measures in community settings. Clinical study registration: German Clinical Trials Register, DRKS-ID: DRKS00013250.